Thermal modification of Eucalyptus grandis wood: Variation of colorimetric parameters - González de Cademartori, Pedro Henrique; Schneid, Eduardo; Gatto, Darci Alberto; Martins Stangerlin, Diego; Beltrame, Rafael (Maderas. Ciencia y Tecnología, 2025)
The color modifications in Eucalyptus grandis thermally modified wood were investigated. One hundred eighty specimens (10 x 10 x 200 mm) were prepared and thermally modified in an electric kiln for 4 and 8 h at 180-240ºC. The color parameters (L*, a*, b*, C*, h* and ΔE) were determined by the CIE-L*a*b* method on radial and tangential sections of untreated and treated wood. The results indicated the darkening of specimens in the radial and tangential sections. Both sections showed variation of L* between 73 and 30, a* between 9 and 5 and b* between 20 and 8. The thermally modified wood at 180 and 200ºC showed similar patterns, equally at 220 and 240ºC. The time of exposure indicated significance just in treatment at 200ºC.